Instagram Media Exposure and Parents' School Choice Decisions: Evidence from an Islamic Primary School - Dewi Septiani; Rani Ade Saputri; Veranus Sidharta (ADPEBI International Journal of Business and Social Science, 2026)
This paper examines the effect of Instagram exposure on parents' school-choice decisions in the context of an Islamic primary school. Purpose – This study seeks to analyze whether exposure to a school's Instagram account significantly influences how parents assess, compare, and ultimately choose a school for their children. Methodology – A quantitative explanatory design was employed to test the relationship between Instagram media exposure (independent variable) and parents' school choice decisions. Data were collected through a structured questionnaire using a five-point Likert scale from 106 respondents, consisting of parents or guardians who had accessed the school's Instagram account and were involved in selecting a school for their children. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression. Findings – Instagram exposure has a positive, statistically significant effect on parents' school choice decisions. The regression equation was Y = 15.829 + 0.710X, with a t-value of 9.941, a significance level of 0.000, and an R-square of 0.492, showing that Instagram exposure contributes meaningfully to parental decision-making. Value – This study highlights Instagram as an important element in the communication ecology of contemporary Islamic primary education, functioning not only as a promotional medium but also as a source of information, visibility, and institutional representation.